Assessing the implementation determinants of antimicrobial stewardship programmes in sub-Saharan Africa through the complexity lens. A CFIR-guided systematic review - Kapatsa, Thandizo; Bwanali, Akim Nelson; Kambewa, Leonard Naphazi; Mkandawire, Vitumbiko; Mwale, Gillian; Harawa, Gracian; Ssebibubbu, Stuart; Ali, Abdisalam Yusuf; Mudenda, Steward; Masi, Abigail; Chumbi, Gertrude; Moyo, Chitemwa; et al. (Frontiers in Microbiology, 2025)
BackgroundAntimicrobial resistance (AMR) poses a significant threat in sub-Saharan Africa (SSA), where fragile health systems and under-resourced facilities exacerbate its burden. Antimicrobial stewardship (AMS) programs have been introduced as a key strategy to optimize antimicrobial use and curb AMR. However, the successful implementation of AMS in SSA remains limited. This systematic review assessed the implementation determinants of AMS programs in SSA using the Consolidated Framework for Implementation Research (CFIR).MethodsA systematic search was conducted across PubMed and Google Scholar for articles published between 2018 and 2024, following PRISMA guidelines. Studies were included if they reported on factors influencing AMS implementation in SSA. Data from 31 eligible studies were extracted and mapped according to the CFIR framework's five domains to identify key barriers and facilitators.ResultsMajor implementation barriers in SSA included underfunded health systems, limited diagnostic and laboratory infrastructure, lack of context-specific AMS guidelines, weak governance and policy enforcement, and insufficient training of healthcare providers. Enablers included hospital leadership support, stakeholder engagement, and existing global frameworks such as the WHO AWaRe guidelines. The review found poor integration of AMS into national health priorities and limited surveillance data, especially at the primary care level.ConclusionAMS implementation in SSA is constrained by systemic, infrastructural, and educational challenges. Strengthening leadership, surveillance systems, healthcare worker training, and the development of context-specific AMS protocols are essential. Effective implementation will require tailored strategies grounded in local realities and supported by strong governance and sustainable funding mechanisms.